Syntactic and Lexical Complexity of Undergraduate Students’ Essays: A Comparison Study between L1 and L2 Writings - Rahayu, Famala Eka Sanhadi; Utomo, Aries; Setyowati, Ririn (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
In measuring learners’ productivity in writing and speaking, there is a formulation known as syntactic and lexical complexity. This study investigates whether there is a difference in syntactic and lexical complexity between L1 and L2 writings or not. This study is quantitative research which employ Web-Based Lexical Complexity Analyser and Web-Based Syntactic Complexity Analyser in order to measure data. The current study results reveal that the p-value of three sub-components of lexical complexity is lower than 0.05 (LD=0.000, LS=0.036, and LV=0.000), which means a significant difference in lexical complexity between L1 and L2 writings. A similar result showed in syntactic complexity where four of five indices of comparing the syntactic complexity of two-language writings showed value <0.05. The p-value of comparing four indices of syntactic complexity such as MLS, DC/C, CP/C, and C/S is 0.006, 0.000, 0.038, and 0.002, respectively. However, the fifth indice, MLC (mean length of clause) shows a p-value >0.05, which means no significant difference between MLC of English writings and Indonesian writings. The study concluded that the students produce more lexical and syntactic complexity in their English writings than in their Indonesian writings.